Analysis of the Role of Skouw PLBN in Handling Drugs Smuggling at The Indonesian Border Papua New Guinea - Imbiri, Isaak Alfret Andris; Hadiwijoyo, Suryo Sakti; Suwartiningsih, Sri (Budapest International Research and Critics University, 2022)
The using of short cut road also become a reason why this kind of crime still exist in the border of Indonesia – PNG. To overcome this issue, Indonesia established a post where cross nation between Indonesia – PNG called PLBN (Pos Batas Lintas Negara) which is located in Skouw, Jayapura. This research aims to analyze the role of PLBN Skouw in order to deal with drug smuggling that taking place in the border of Indonesia – PNG. This research is using qualitative method which is trying to looking for the answer by collecting the datas and filtering them to support the argument that already contructed. Besides, this research also applying National Security Theory, Border Security and Drug Trafficking Concept. Furthermore, this research shows that PLBN Skouw has the role to deal with drug smuggling issue in the border of Indonesia – PNG. The roles are as regulator, overseer and center of border mobility. However, the role as center of border mobility did not meet the expection, meanwhile the role as regular and overseer were performed optimally enough.